Healthy Lives 5 Axis Scale for individuals with complex health and social needs: assessment of validity and reliability - Henry White; Peter Gonzalez; Sagi Shashar; Zoe Silver; Hannah Scott; Victor Novack (BMC Health Services Research)
Abstract Background The field of complex care management for patients with urgent health and social challenges has rapidly grown, leading to calls for improved tools for measuring quality and outcomes. Most available measures were not developed specifically for a clinical context with a population with complex needs. The Healthy Lives 5 Axis Scale (HL-5) was created to fulfill this role. This concise, multidimensional scale measures key domains, including health-related functioning, physical and social needs, capacity for self-care, access, and utilization. The purpose of this study was to determine the interrater and test–retest reliability and the construct and concurrent validity of the HL-5. Methods The study population included adults who attended an appointment with a primary care physician at an urban community health center. The reliability assessment of the HL-5 questionnaire included test–retest ratings by the same scorer and between two different scorers. Criterion convergent validity was evaluated by comparing the HL-5 domains with relevant domains of external questionnaires using Pearson correlation coefficients (r). The comparison measures have a strong evidence base, are widely used, and are nonproprietary. Results There were 64 participants, with a mean age of 39.1. Test–Retest Reliability, measured by the intraclass coefficient (ICC), was greater than 0.8 for Functioning, Needs, Utilization, and Access, indicating very strong internal consistency and 0.754 for Self-Care, representing good internal consistency. Criterion Validity for the axes, assessed by each axis’ correlations with a criterion measure, was statistically significant at of p < 0.05. Conclusions This study of the psychometric properties of the Healthy Lives 5 Axis Scale (HL-5) demonstrated its value for assessing patients’ complex health and social needs. It showed high levels of reliability in a clinical setting with a diverse patient populations and strong correlations with well-established measures of functioning, needs, self-care, access, and utilization. HL-5 requires only a few minutes to complete and yields actionable results, demonstrating its potential for integration into the workflow of a primary care practice or care management program.